2021
DOI: 10.9734/jpri/2020/v32i4331073
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Distance between Vibrating Line and Fovea Palatinae in Class I, Class II and Class III Soft Palate Types

Abstract: Objective: The objective of this study was to evaluate the mean distance between the vibrating line and fovea palatinae in Class I, Class II and Class III Soft Palate types. Methodology: This study was conducted at Dr. Ishrat-ul-Ebad Khan Institute of Oral Health Sciences Karachi among 197patients. Duration of study was six months. All patients were examined for vibrating line clinically, assessed using phonation method. Subsequently, distance between vibrating line and fovea paltatinae was measured with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Landmarks like fovea palatine and vibrating line helps in exact placement of posterior denture borders however, the different soft palatal shapes show positional variation of vibrating line. 10 Research work by Baharat Kumar 17 and coworkers on 197 subjects reported anteriorly located vibrating line in 64% patient whereas 34 % had line coincide with fovea. None of their subjects had posterior location.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Landmarks like fovea palatine and vibrating line helps in exact placement of posterior denture borders however, the different soft palatal shapes show positional variation of vibrating line. 10 Research work by Baharat Kumar 17 and coworkers on 197 subjects reported anteriorly located vibrating line in 64% patient whereas 34 % had line coincide with fovea. None of their subjects had posterior location.…”
Section: Discussionmentioning
confidence: 98%
“…Gender based difference in locating vibrating line had been studied in different populations around the world 16,17 . Alous 18 reported insignificant gender-based difference with vibrating line location with respect to fovea.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations